The Heat Treatment Influence of 1.3343 High Speed Steel on Content of Residual Austenite. (2016) - Stoicanescu, Maria; Ene, Emilian; Zara, Adriana; Giacomelli, Ioan; Crisan, Aurel
Abstract: The heat treatment applied to high speed steel is in large measure dictated by the necessity of decreasing the residual austenite content. After hardening, a large amount of residual austenite it is found in the structure; this is unwanted because it is less hard than practical necessities and also unstable in time. As a result, the heat treatment has the purpose to conferee to tools mechanical properties that are required in exploitation, and in the same time, stable from structural point of view and of mechanical characteristics. In this purpose there are known several processes, as for example multiple tempering and treatment below zero degrees. In this paper, it is proposed the analysis of residual austenite from 1.3343 high steel speeds subject to multiple heat treatment operations, by determining after each, the quantity of residual austenite; this was made with X ray diffraction using a software package program. Research has revealed the decrease of residual austenite content with the number of tempering as well as with the treatment below zero degrees.